If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2h + 12 = 3 Reorder the terms: 12 + 2h = 3 Solving 12 + 2h = 3 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2h = 3 + -12 Combine like terms: 12 + -12 = 0 0 + 2h = 3 + -12 2h = 3 + -12 Combine like terms: 3 + -12 = -9 2h = -9 Divide each side by '2'. h = -4.5 Simplifying h = -4.5
| -138=-6x-5(-4x+8) | | 28/30=x/4 | | -x=18-3x | | -6+x=-2x+6 | | 5=3+8 | | 7n-3=-9+4n | | m+4=-19 | | x+8=-42 | | 7s-13=-49+s | | 5x-30+30x=10+3x-20 | | 23x-17y=19 | | 12x-3=7x+6 | | 8/3=x | | 3x(5-6)=15 | | -8x^3-72x=0 | | .25x+9=-16 | | t/-8=-5 | | -6x-21=-129 | | (12/x)-(12/x-5)=2/x | | 95=4-9x | | -x-2=-3+4 | | 17/7=y/6 | | y-16=z | | 3:1/5 | | x-10=.85x | | -3x^2-11x+8=0 | | 1588=-x^2-4x-8 | | 8/3+x=-14 | | 7+2x+x+8+3-x=4x+11+2-x+2-x+4x+11 | | 13-2x=4x+10 | | y+-7=28 | | 15+11= |